Transnational Chicanx perspectives on Ana Castillo - Hernández, Bernadine Marie; Roybal, Karen R. (University of Pittsburgh Press, 2021)
Transnational Chicanx Perspectives on Ana Castillo is the first edited collection that focuses on Castillo's oeuvre, which directly confronts what happens in response to cultural displacement, mixing, and border crossing. Divided into five sections, this collection thinks about Castillo's poetics, language, and form, as well as thematic issues such as borders, immigration, gender, sexuality, and transnational feminism.
Keywords: Castillo, Ana -- Criticism and interpretation.; Castillo, Ana; Transnationalism in literature.; Feminist literature -- History and criticism.; Hispanic Americans in literature.; Mexican Americans in literature.; American literature -- Hispanic American authors -- History and criticism.; Transnationalisme dans la littérature.; Féminisme -- Documentation -- Histoire et critique.; Américains d'origine latino-américaine dans la littérature.; Américains d'origine mexicaine dans la littérature.; Littérature américaine -- Auteurs américains d'origine latino-américaine -- Histoire et critique.; Transnationalism in literature; Mexican Americans in literature; Hispanic Americans in literature; Feminist literature; American literature -- Hispanic American authors; Criticism, interpretation, etc.; Literary criticism.; Critiques littéraires.